THE IMPORTANCE OF FOREST FIRE PREVENTION ACTIVITIES: ENVIRONMENTAL EDUCATION AS A TOOL FOR FOREST FIRE PREVENTION IN CANAÃ DOS CARAJÁS - Pimentel da Silva, Helton (Revista Gênero e Interdisciplinaridade, 2024)
This study addresses the importance of forest fire prevention and combat activities, emphasizing environmental education as a tool for preventing forest fires in Canaã dos Carajás. The social relevance of the topic is highlighted by the significant impact of forest fires on the environment, economy, and public health, especially in the context of the Amazon Rainforest, which is essential for global climate regulation. The research is descriptive and combines data collection methods, including document analysis and semi-structured interviews. The document analysis involves reviewing reports, public policies, scientific articles, and educational materials, while the interviews are conducted with a representative sample of residents, educators, local authorities, and civil defense professionals. The general objective of the study is to analyze the effectiveness of environmental education activities in preventing forest fires. The specific objectives include analyzing residents’ perceptions of the importance of prevention, the influence of public policies, and proposing improvements in environmental education strategies. The research identified the urgent need for effective conservation policies, given the importance of the Amazon Rainforest in climate regulation. In Canaã dos Carajás, rapid urbanization driven by mining and a lack of resources and infrastructure are critical challenges for forest fire prevention. The interdisciplinary approach, using qualitative and quantitative techniques, allowed for a detailed analysis of the challenges faced and best practices. Location maps and satellite images were used to analyze the distribution of fire outbreaks. The results underline the importance of an integrated approach to fire prevention, highlighting the effectiveness of public policies and the need for ongoing training. This study provides valuable contributions to the formulation of public policies and educational strategies, promoting environmental education and active community involvement as key elements for effective forest fire prevention.